(untitled) (DAPesquisa, 2021)
The present work proposes to interrogate, based on a photographic production and a later reflexive tour, the existing relationships between the ruins of the Historic Center of São Luís and the records that, through graffiti and “pichações/pichações”, young people from the periphery have carried out on the walls, doors and windows of historic houses in the capital of Maranhão, Brazil. The methodology used for the production and inventory of the research images is based on a visual anthropology and an anthropology of the image. From the point of view of the way of operating the thought, I use some ideas of the philosopher Walter Benjamin (2012, 2009, 2013) about photography, remembrance and allegory. Lastly, I produce some commentaries on the meanings and aesthetic/political powers of graffiti and “pichações/pichações” in the Historic Center of São Luís - MA and the correspondence established with the ruins of the houses present there. The text is not intended as revisionist of themes related to graffiti, pichações/pixações and heritage, but a critical essay regarding how the visual arts operate in the context of the correspondence between abandonment and appropriation of public space.